Performance of Lambs Born to Energy- and Protein-Supplemented Ewes During Gestation and Lactation - N. C. Silva; S. L. S. Cabral Filho; I. O. M. A. Freitas; F. C. Rocha; A. M. Azevedo; V. R. Rocha Júnior; M. D. Ribeiro (Faculty of Animal Science, IPB University, 2026)
Maternal nutrition and supplementation during gestation and lactation improve fetal development, survival, and growth of lambs. The aim of this study was to evaluate the effects of energy and protein supplementation in the diet before, during, and in the final third of gestation and lactation, within a synchronized breeding system, on the health and performance of lambs. Forty Santa Inês × Dorper ewes, averaging ten months of age and two previous births, were distributed in a completely randomized design with four treatments: mineral supplementation only, supplementation initiated before breeding, supplementation starting after pregnancy confirmation, and supplementation restricted to late gestation. Supplements were provided daily at 4 pm at 1% of body weight (BW), adjusted every 15 days when ewes were weighed. The experimental period lasted 60 days, with 10 days of adaptation. Variance analysis was performed in subdivided plots, and the means were compared using Tukey's test at 5% probability. Concentrated supplementation altered (p<0.0072) birth weight 3.79 kg, colostrum intake, daily gain (p<0.0028) 242.39 g/animal/day, morphometric measurements, eggs per gram of feces, protein and energy metabolic profiles, and cortisol levels in lambs. There was no difference in lambing rate, litter type, sex, fecal score, or mineral metabolism. However, supplementation begun 20 days before breeding and after pregnancy confirmation improved anthelmintic response 272.49 EPG and produced heavier lambs at weaning 20.78 kg. Maternal energy and protein supplementation, especially when started before breeding or after pregnancy confirmation, improves lamb growth, metabolic status, and parasitic resistance.